EVALUASI PROSEDUR PENYIMPANAN DAN PENDISTRIBUSIAN SEDIAAN FARMASI DAN BAHAN MEDIS HABIS PAKAI DI PUSKESMAS PEKAUMAN BANJARMASIN - Noor Aisyah; Eka Kumalasari; Merina Hariani; Rina Feteriyani (Jurnal Insan Farmasi Indonesia, 2022)
Storage and distribution are management activities of pharmaceutical preparations and medical consumables in storing and distributing to pharmaceutical service sub-units to avoid expired date. The purpose of this study was to determine the procedure and the percentage of suitability of storage and distribution of pharmaceutical preparations and medical consumables at Banjarmasin's Pekauman Health Center. This type of research is non - experimental with descriptive observative. Data collection using the prospective method. The population in this study is the room and all data storage and distribution of pharmaceutical preparations and medical consumables, with saturated sampling period March-April 2020. The research data was observed for qualitative results and calculated by percentage analysis for quantitative results. The results showed that the storage procedures for pharmaceutical preparations and BMHP were 90% in accordance with the Technical Guidebook for Pharmaceutical Service Standards in Puskesmas and 86.11% in accordance with the Checklist for Quality Assurance of Pharmaceutical Services in Basic Health Services. And the procedures for distributing pharmaceutical preparations and medical consumables at the Banjarmasin Pekauman Health Center 100% in accordance with the Technical Guide to Pharmaceutical Services Standards at the Health Center and the Quality Assurance Checklist for Pharmaceutical Services in Basic Health Services.